Latter-day Screens : Gender, Sexuality, and Mediated Mormonism - Weber, Brenda R., 1964- (Book collections on Project MUSE., 2019)
Brenda R. Weber examines the ways in which the mediation of Mormonism through film, TV, blogs, YouTube videos, and memoirs functions as a means through which to understand conversations surrounding gender, sexuality, spirituality, capitalism, justice, and individualism in the United States.